Penerapan Strategi Pemasaran Digital Melalui Media Sosial Pada Usaha Pangkas Rambut Cemerlang - Golan Hasan; Erika Erika (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Cemerlang Barbershop is one of the hair barber businesses in Batam City. The problem at Cemerlang Barbershop is that there is a decrease in the number of visitors and the names of partners are not yet widely known, so the focus and aim of this service is to help Cemerlang Barbershop’s problems through creating social media accounts in the form of Instagram and Tiktok as well as making business cards. The methods used are interview and observation methods. The results obtained are that promotions carried out on social media have proven to be helpful in making the name Cemerlang Barbershop better known and making it easier to reach the desired consumers. Then the business cards created also increased brand awareness and increased the number of visitors from previously 10 visitors coming to 20 visitors. So it can be concluded that this service activity was successful in helping the problems experienced by Cemerlang Barbershop partners.